Structural transformation of tungsten oxide nanourchins into IF–WS2 nanoparticles: an aberration corrected STEM study - Deepak, Francis Leonard; Castro Guerrero, Carlos Fernando; Mejía Rosales, Sergio; Yacamán, Miguel José (Royal Society of Chemistry, 2011)
IF–WS2 nanoparticles synthesized starting from tungsten oxide nanourchins have been investigated by using aberration corrected scanning transmission electron microscopy (Cs-STEM). The synthesis process produced IF–WS2 nanoparticles of two different and well differentiated ranges of size. High resolution HAADF–STEM images and their comparison with simulated STEM micrographs reveal the predominance of stacking of the type 1T close to the border of the structure; the observation of this kind of stacking, observed previously in IF–MoS2 but never reported before in the case of the IF–WS2 nanostructures, adds a new dimension to the existing understanding of structure and stacking in the case of the nanostructures of transition metal chalcogenides